White light emission from alternating current organic light‐emitting devices using high frequency color‐mixing. Issue 11 (21st August 2013) - Fröbel, Markus; Perumal, Ajay; Schwab, Tobias; Fuchs, Cornelius; Leo, Karl; Gather, Malte C.
<x xml:space="preserve">Abstract</x> We report on a novel approach to obtain white emission from organic light‐emitting devices, which require no charge injection from external electrodes and instead use a capacitively coupled alternating current driving signal for device operation. In our approach, both half‐cycles of a sinusoidal driving signal are used to independently address a phosphorescent green and a triplet‐harvesting blue/red unit. Both emission units are spatially separated and connected by sharing a common n‐doped electron transport layer. Upon application of a sinusoidal driving voltage, the device alternately emits green and purple light pulses with durations of 25% of the signal period. For high frequencies, the human eye cannot resolve this modulation and the emitted light is perceived as white. This approach yields devices with warm‐white color coordinates (0.43, 0.44), a CRI of 76.5, and high brightness values of 1000 cd m−2. We show evidence proving that the devices operate on a capacitive‐coupling based driving scheme and that the emission is solely due to charge carriers provided by the doped transport layers. High dielectric constant insulating layers between electrodes and organic layers efficiently suppress charge carrier injection and improve the Zener tunneling mechanism that is required to replenish the depleted transport layers after each emission cycle.